(3eZGfi GdebGeGJ aj eYGfi GdebGeGJs - (3JGL GdOjf eMeO Hf YHO GdQMef GdeSYhOi GdHfLOjgis; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s ((3CMeO Hf eMeO GdLOhQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi NeQ CSGLjY Gdcde ai VeGFQ GdaUMGA , haLQ jfGHjY GdMce ef HUGFQ GdfUMGA s
(3BNQgG (B:s
(3abO JSLY GdhQbGA hgj MeGeI , hbO JfWb GdChJGQ hgj LeGO Je GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GdCOHs